A critical test of Drosophila anaesthetics: Isoflurane and sevoflurane are benign alternatives to cold and CO2. (August 2017) - MacMillan, Heath A.; Nørgård, Mikkel; MacLean, Heidi J.; Overgaard, Johannes; Williams, Catherine J.A.
Graphical abstract: Highlights: CO2 and cold are often used to anaesthetize insects, but have side-effects. We tested the effects of four anaesthetics on several Drosophila phenotypes. Isoflurane and sevoflurane appear to have minimal impact on organismal traits. In many cases, CO2 and cold can still be used if ample time is given for recovery. Abstract: Anaesthesia is often a necessary step when studying insects like the model organism Drosophila melanogaster . Most studies of Drosophila and other insects that require anaesthesia use either cold exposure or carbon dioxide exposure to induce a narcotic state. These anaesthetic methods are known to disrupt physiology and behavior with increasing exposure, and thus ample recovery time is required prior to experimentation. Here, we examine whether two halogenated ethers commonly used in vertebrate anaesthesia, isoflurane and sevoflurane, may serve as alternative means of insect anaesthesia. Using D. melanogaster, we generated dose-response curves to identify exposure times for each anaesthetic (cold, CO2, isoflurane and sevoflurane) that allow for five-minutes of experimental manipulation of the animals after the anaesthetic was removed (i.e. 5 min recovery doses). We then compared the effects of this practical dose on high temperature, low temperature, starvation, and desiccation tolerance, as well as locomotor activity and fecundity of female flies following recovery from anaesthesia. Cold, CO2 and isoflurane each had significant or near significant effects on the traits measured, but the specific effects of each anaesthetic differed, and effects on stress tolerance generally did not persist if the flies were given 48 h to recover from anaesthesia. Sevoflurane had no measureable effect on any of the traits examined. Care must be taken when choosing an anaesthetic in Drosophila research, as the impacts of specific anaesthetics on stress tolerance, behavior and reproduction can widely differ. Sevoflurane may be a practical alternative to cold and CO2 anaesthesia in insects – particularly if flies are to be used for experiments shortly after anesthesia.